Study of Teakwood Quality from Community Forests in Gunungkidul. VII. Natural Subterranean Termite Resistance - Ganis Lukmandaru; Pito Wargono; Arsy Rahman Mohammad; Vendy Eko Prasetyo (Jurnal Ilmu Kehutanan)
Teak wood has been used for various uses because of its excellent natural durability as well as beautiful grain and colour of its heartwood. However, variability in natural durability exists between trees of different geographical zones. The previous paper in this series reported on the chemical properties of teak wood from different zones (Nglipar, Panggang, and Playen). In this study, as a continuation, natural termite resistance of teak wood grown in community forests of Gunungkidul and the factors correlating to the termite resistance i.e. chemical and colour properties, were determined. Further, the data obtained here were compared with that of wood samples from Perhutani forest plantation (Randublatung site). No-choice termite feeding test by using a subterranean termite Coptotermes curvignathus were conducted on wood samples taken from three trees of three planted sites. The colour properties of each sample were measured using the CIELAB (L*, a*, b*) system. The chemical and colour characteristics results then were correlated with the mass loss of wood and survival rate of termites after 13 days of feeding. The heartwood and sapwood of all of the trees tested exhibited antitermitic activities. Significant differences were found in survival rate of termites due to interaction of the site and radial position. Samples from Panggang had larger termite resistance judging by its survival rate of termites. Further, the heartwood regions of Panggang and Playen sites exhibited higher antitermite activities than those of Randublatung samples. Measurements of colour showed that no significant differences were found between outer and inner heartwood parts. Samples from Playen showed the lightest on the basis of the sites. In the combined sapwood and heartwood data, mass loss was positively associated with hot-water solubility levels and negatively with ethanol-toluene extractive content. In addition, pH values moderately correlated with survival rate on 8-day observation. With regard to colour properties, it was measured that larger a* values (redness) induced larger mass loss of heartwood.